The Traditional Belief in John Knox’s House at the Netherbow vindicated. (In reply to Two Papers read to the Society of Antiquaries by Robert Miller, Esq., F.S.A. Scot.) - Guthrie, Charles J (Proceedings of the Society of Antiquaries of Scotland, 1899)